2008
DOI: 10.1007/s11302-008-9124-0
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid variations resulting in functional and nonfunctional zebrafish P2X1 and P2X5.1 receptors

Abstract: Several zebrafish P2X receptors (zP2X 1 , zP2X 2 , and zP2X 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…In fact, several studies have demonstrated the existence of duplicated genes in zebrafish (Amores et al, 1998;Rosemberg et al, 2007). Concerning purinergic signaling, it has been recently reported that the zebrafish family of ionotropic P2X receptors is comprised of nine members with two paralog copies of P2X 3 , P2X 4 , and P2X 5 (Low et al, 2008). The NTPDase7 ortholog was not detected in zebrafish, which lead us to hypothesize that its respective gene might not yet have been characterized or even that this member might have been lost from the zebrafish genome during evolution.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have demonstrated the existence of duplicated genes in zebrafish (Amores et al, 1998;Rosemberg et al, 2007). Concerning purinergic signaling, it has been recently reported that the zebrafish family of ionotropic P2X receptors is comprised of nine members with two paralog copies of P2X 3 , P2X 4 , and P2X 5 (Low et al, 2008). The NTPDase7 ortholog was not detected in zebrafish, which lead us to hypothesize that its respective gene might not yet have been characterized or even that this member might have been lost from the zebrafish genome during evolution.…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, two paralogous P2X5 genes have been reported. zP2rx5.1 was mapped on chromosome 5, and zP2rx5.2 (also known as zP2rx514 or zP2rx8) is located on chromosome 15 [ 57 , 429 , 490 ]. The zP2rx5.1 receptor is the only zP2X receptor for which mRNA has been detected in embryonic skeletal muscle, whereas zP2rx5.2 mRNA, like other zP2X receptor mRNAs, was found in the nervous system [ 429 , 490 , 491 ].…”
Section: Physiological Functions Of P2x Receptors Inferred From Genetmentioning
confidence: 99%
“…zP2rx5.1 was mapped on chromosome 5, and zP2rx5.2 (also known as zP2rx514 or zP2rx8) is located on chromosome 15 [ 57 , 429 , 490 ]. The zP2rx5.1 receptor is the only zP2X receptor for which mRNA has been detected in embryonic skeletal muscle, whereas zP2rx5.2 mRNA, like other zP2X receptor mRNAs, was found in the nervous system [ 429 , 490 , 491 ]. Using morpholino-mediated zP2rx5.1 gene knockdown, it was demonstrated that the zP2rx5.1 receptor is necessary for the muscle responsiveness to ATP but is not essential for myogenesis during zebrafish embryonic development [ 490 ].…”
Section: Physiological Functions Of P2x Receptors Inferred From Genetmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, all neurons fall into three groups—those expressing only one of the subunits or those expressing both 87. zP2X 1 and zP2X 5:1 receptors produced substantial currents when expressed by Xenopus oocytes, but the zP2X 2 receptor appeared to be nonfunctional 88. They also showed that embryonic skeletal muscle expressed only one P2X receptor, namely P2X 5.1 and that antisense knockdown of P2X 5.1 eliminated skeletal muscle responsiveness to ATP, although it did not prevent myogenesis.…”
Section: Lower Vertebratesmentioning
confidence: 99%